(untitled) (American Journal of Innovation in Science and Engineering, 2022)
Buildings represent the identity of cities and create the memory of the nation. Architecture landmark are the ambassadors of culture and civilization of the country. The UAE modern heritage represented in the 60s, 70s, and 80s architecture signifies the memory of the country and highlights the architecture style and its influences in various periods. The national theatre of Abu Dhabi is a key landmark from the 70s era. This cultural symbol is a landmark that shaped the style of the capital city at this time. This paper is a case study that aims at understanding the architecture of the National Theatre of Abu Dhabi building as a symbol of architecture and the architect’s only building remaining in the region. The paper outcomes and findings represent an approach for evaluating and greening modern heritage buildings in the Middle East while protecting both their historical and cultural values. The research aims to provide architects, researchers, and decision makers with a capture of architectural heritage buildings documentation via BIM modelling and traditional methods.